Preoperative Physical Activity Level and Exercise Prescription in Adults With Obesity: The Effect on Post-Bariatric Surgery Outcomes - Jabbour, Georges; Ibrahim, Rony; Bragazzi, Nicola (Frontiers in Physiology, 2022)
This systematic review summarizes current evidence on the relation between pre-operative physical activity (PA) levels with bariatric surgery (BS) outcomes, and on the beneficial role of pre-operative exercise/PA program among BS candidates. This systematic review suggests that candidate patients accumulating pre-operative PA level improved several BS outcomes. These improvements were reported mainly for anthropometric and cardiometabolic parameters, physical function, and quality of life. Observed improvements manifested during a distinct period of time in response to a wide variety of exercise programs. Evidence on pre-operative PA level as well as on pre-operative exercise implementation on BS outcomes is advocated despite the small number of participants and lack of control. Thus, further studies are required to explore the most effective and suitable form of exercise prescription prior to BS while considering physical and psychological limitations of obese patients.